Tangible economic value of non-timber forest products from peat swamp forest in Kampar, Indonesia - Bintang Charles Hamonangan Simangunsong; Elisa Ganda Togu Manurung; Elias Elias; Manuntun Parulian Hutagaol; Jusupta Tarigan; Sigit Baktya Prabawa (Society for Indonesian Biodiversity, 2020)
Abstract. Simangunsong BCH, Manurung EGT, Elias, Hutagaol MP, Tarigan J, Prabawa SB. 2020. Tangible economic value of non-timber forest products from peat swamp forest in Kampar, Indonesia. Biodiversitas 21: 5954-5960. Development of alternative economy based on non-timber forest products usage is an important means to prevent forest conversion and preserve the quality of a forest ecosystem. The main objectives of this study were to identify and calculate the economic value from tangible/marketable perspective of the non-timber forest products (NTFPs) provided by peat swamp forest in Kampar, Sumatra, Indonesia. This is one of the largest remaining peat swamp forest ecosystems in the country. Seven villages located around that forest ecosystem with total forest cover area of 201,224 ha were chosen as samples. A conversion return approach was used to estimate the economic value of non-timber forest products. The results showed 18 kinds of non-timber forest products were identified, but only seven were used commercially by community. They are jungle rubber (Hevea brasiliensis), sago (Metroxylon sp.), swiftlet nest (Aerodramus fuciphagus), honey, betel nut (Areca catechu L), Agathis resin (Agathis dammara), and pandan (Pandanus amaryllifolius Roxb.) The obtained economic value of NTFPs was very low, which was about Rp 9,367.4 (or US0.68 ha-1 yr-1). Market development of non-timber forest products is then crucial, and the government should play an important role in promoting it in collaboration with private companies. Non-marketed non-timber forest products and various environmental services should also be taken into account to measure that peat swamp forest ecosystem value. Otherwise, concerns about the sustainability of that forest ecosystem in Indonesia due to undervaluation of forest resources will continue.